2022
DOI: 10.3389/fonc.2022.897700
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of gradient-based segmentation for measuring metabolic parameters influenced by uptake time on 18F-PSMA-1007 PET/CT for prostate cancer

Abstract: PurposeTo determine an optimal setting for functional contouring and quantification of prostate cancer lesions with minimal variation by evaluating metabolic parameters on 18F-PSMA-1007 PET/CT measured by threshold-based and gradient-based methods under the influence of varying uptake time.Methods and materialsDual time point PET/CT was chosen to mimic varying uptake time in clinical setting. Positive lesions of patients who presented with newly diagnosed disease or biochemical recurrence after total prostatec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…If a convincing anatomical correlate was visible on MRI or diagnostic CT, a focal boost on the GTV could be considered, preferably in the context of a clinical trial. Delineation of the GTV should be based on the anatomical imaging, and not on the PSMA-avid region as there are currently no validated gradient- or threshold-based segmentation methods [19] . This poses a risk of underestimating or overestimating the size of the tumor, with consequent dosing errors and a potential impact on tumor control as well as toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…If a convincing anatomical correlate was visible on MRI or diagnostic CT, a focal boost on the GTV could be considered, preferably in the context of a clinical trial. Delineation of the GTV should be based on the anatomical imaging, and not on the PSMA-avid region as there are currently no validated gradient- or threshold-based segmentation methods [19] . This poses a risk of underestimating or overestimating the size of the tumor, with consequent dosing errors and a potential impact on tumor control as well as toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Giesel et al reported higher uptake in suspected malignant lesions at 3 h compared to 1 h, but no difference in the number of lesions, in 12 patients with BCR (Giesel et al 2018 ). Lau et al reported no difference in the number of found extra-prostatic lesions in 68 patients scanned at a mean 94 and 144 min after injection (Lau et al 2022 ). The focus of their study was delineation of lesions, so the results cannot readily be used for determining optimal uptake time.…”
Section: Discussionmentioning
confidence: 99%
“…Lau et al [101] included 275 lesions in 68 patients diagnosed with biochemical recurrence after total prostatectomy. The authors measured metabolic parameters on [ 18 F]PSMA-1007 dual time point PET/CT images using threshold-based and slope-based methods under different acquisition times.…”
Section: Segmentationmentioning
confidence: 99%